Teacher Strategies for Fostering Discipline Character among Fifth-Grade Elementary School Students - Desak Ketut Sriwati; Kasmawati Kasmawati; Chairan Zibar L. Parisu (CV. Gerasi Insan Nusantara, 2025)
Fostering discipline is an essential component of elementary education because it supports effective learning, personal responsibility, and the development of positive character. Nevertheless, schools continue to encounter challenges in developing students' discipline, including inconsistent compliance with school regulations, tardiness, limited responsibility in completing assignments, and inadequate awareness of maintaining order in the learning environment. This study aimed to examine the strategies employed by teachers to foster discipline among fifth-grade students and to describe the changes in students' disciplinary behavior resulting from the implementation of these strategies. A qualitative descriptive approach was employed. Data were collected through observations, interviews, and documentation involving the principal, the fifth-grade teacher, and students as research informants and data sources. Data were analyzed through data reduction, data display, and conclusion drawing, while data credibility was established through source and methodological triangulation. The findings revealed that teachers fostered student discipline through habituation in daily routines, role modeling, guidance and advice, supervision, positive reinforcement, and consistent implementation of school rules. These strategies contributed to the development of students' disciplinary behavior, as reflected in improved punctuality, greater compliance with school and classroom regulations, increased responsibility for completing assignments, and greater awareness of cleanliness and order in the school environment. The study concludes that teacher strategies implemented consistently, continuously, and through an integrated approach can support the development and internalization of discipline as an important character value among elementary school students.